Obtenção e evolução da fase icosaedral quasicristalina em ligas Al-Cu-Fe e Al-Cu-Fe-B por Melt-Spinnin - Feitosa, Francisco Riccelly P. (2009)
Melt spinnng processing is one of the most common processes to obtaining quasicrystaline structures. This is because of the fast cooling rate it imposes on the system, favoring such type of structure. This work deals with the production of quasycristaline phases (Al60Cu27,5Fe12,5 e Al57Cu27,5Fe12,5B3) via melt-spinning. The alloys were initially cast via induction melting under atmospheric air, with the designed chemical composition of the quasicrystals. Hence, the ribbons were produce by melt-spinning were characterized by means of x-ray diffraction and scanning electron microscopy. The results indicate that the icosahedral ψ - Al65Cu20Fe15 phase formed in both types of starting compositions. It seams that the boron contributes to stabilize the icosahedral phase.